2014
DOI: 10.1002/bio.2721
|View full text |Cite
|
Sign up to set email alerts
|

Novel Na+ doped Alq3 hybrid materials for organic light‐emitting diode (OLED) devices and flat panel displays

Abstract: Pure and Na(+) -doped Alq3 complexes were synthesized by a simple precipitation method at room temperature, maintaining a stoichiometric ratio. These complexes were characterized by X-ray diffraction, Fourier transform infrared (FTIR), UV/Vis absorption and photoluminescence (PL) spectra. The X-ray diffractogram exhibits well-resolved peaks, revealing the crystalline nature of the synthesized complexes, FTIR confirms the molecular structure and the completion of quinoline ring formation in the metal complex. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 29 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Research speaks volumes on novel complexes of doped quinoline complexes that emit light in various regions of the visible spectrum. [ 64–67 ]…”
Section: Luminous Paints – a Novel Application Of Persistent Phosphormentioning
confidence: 99%
“…Research speaks volumes on novel complexes of doped quinoline complexes that emit light in various regions of the visible spectrum. [ 64–67 ]…”
Section: Luminous Paints – a Novel Application Of Persistent Phosphormentioning
confidence: 99%
“…Hence it is proposed to synthesize and characterize iron doped Alq 3 , which is generally used as electron transport or emission layer iron doped Alq 3 . The main focus of OLED investigation has been to address this issue to conjugate organic polymer as aluminum tri hydroxyl quinoline (Alq 3 ) [14][15][16][17]. An attempt is made to increase the performance, lifetime and temperature stability of the luminescent materials for OLEDs, solid state lightning, PLLCD.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have proposed the use of hybrid (organometallic/inorganic) composites to overcome these issues. Besides, those hybrids showed significant improvements in mechanical strength, thermal stability, luminescent efficiency, and charge mobility when compared to pure Alq3 [ 15 , 16 ]. Cuba et al [ 17 ] showed that Alq3-ZnO composites exhibited enhanced luminescence properties and a slight shift from green emission to greenish blue.…”
Section: Introductionmentioning
confidence: 99%